Géopolitiques populaires, géopolitique des médias et bande dessinée - Maksa, Gyula; Lukács, Laura Klára (Acta Romanica Quinqueecclesiensis : La publication du Département d’Études Françaises et Francophones, Université de Pécs, 2025)
The study explores the geopolitics of comics as a medium shaped by global media power relations. Drawing on Philippe Boulanger’s theory of media geopolitics, it identifies three main centers of influence—Europe, North America, and East/Southeast Asia—reflected in the traditions of bande dessinée, comics, and manga. The authors highlight transnational exchanges, media cities, cultural hybridization, and the role of comics in “soft power” diplomacy and popular geopolitics.